The Moore-Penrose inverse of 2 x 2 matrices over a certain *-regular ring - Zhu, Huihui (2014)
In this paper, we study representations of the Moore-Penrose inverse of a 2 x 2 matrix M over a *-regular ring with two term star-cancellation. As applications, some necessary and sufficient conditions for the Moore-Penrose inverse of M to have different types are given.